2020
DOI: 10.1182/blood-2020-142917
|View full text |Cite
|
Sign up to set email alerts
|

VWF/ADAMTS13 Ratios Are Potential Markers of Immunothrombotic Complications in Patients with COVID-19: A Cross-Sectional Study

Abstract: BACKGROUND. COVID-19 is a prothrombotic disease, characterized by both arterial and venous thrombosis. The pathogenesis of coagulopathy in COVID-19 is multifactorial, with activation of endothelial cells, platelets, neutrophils, and other immune system effectors playing crucial roles. High levels of von Willebrand factor (VWF) and reduced levels of ADAMTS13 have been observed in COVID-19, sepsis, and immunothrombotic states, and an elevated VWF/ADAMTS13 ratio has been previously described in ischemic stroke1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…IL-6 soluble IL-6 receptor (sIL-6R) complex triggers release of ULVWF multimers from endothelial cells, but to a lesser extent than IL-8 or TNF-α (Kichloo et al, 2020).. Conversely, IL-6 inhibits a ADAMTS13 and thus reducing ULVWF multimer cleavage and enhancing platelet adhesion and aggregation (Kichloo et al, 2020). Our study revealed that higher mean Vwf/ADAMTS13 Ratio correlated with COVID-19 severity and this is consistent with the study by Madeeva et al (2020) who reported an increase in VWF antigen and a reduction in ADAMTS13 activity in COVID-19 patients, which is related to disease severity and could predict poor clinical outcomes. They also suggested that the ADAMTS13 activity reduction could be a marker associated with COVID-19 compared to other non-critical medical conditions.…”
Section: Discussionsupporting
confidence: 88%
“…IL-6 soluble IL-6 receptor (sIL-6R) complex triggers release of ULVWF multimers from endothelial cells, but to a lesser extent than IL-8 or TNF-α (Kichloo et al, 2020).. Conversely, IL-6 inhibits a ADAMTS13 and thus reducing ULVWF multimer cleavage and enhancing platelet adhesion and aggregation (Kichloo et al, 2020). Our study revealed that higher mean Vwf/ADAMTS13 Ratio correlated with COVID-19 severity and this is consistent with the study by Madeeva et al (2020) who reported an increase in VWF antigen and a reduction in ADAMTS13 activity in COVID-19 patients, which is related to disease severity and could predict poor clinical outcomes. They also suggested that the ADAMTS13 activity reduction could be a marker associated with COVID-19 compared to other non-critical medical conditions.…”
Section: Discussionsupporting
confidence: 88%
“… 6 This protease was found to be insufficient when tested in severe COVID-19 patients. 82 , 83 , 90 , 96 , 98 This important proteolytic enzyme is needed to cleave the excess ULVWF multimers that are released from damaged ECs and to prevent microthrombogenesis.…”
Section: Hemostatic Pathogenesis Of Covid-induced Endotheliopathymentioning
confidence: 99%
“…ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) is responsible for cleaving ULvWF into smaller pieces, thereby reducing its plasma levels and activity. Elevated vWF/ADAMTS-13 ratios have been observed in sepsis and COVID-19 and are positively correlated with high ICU mortality [6,7]. Recently, the vWF/ADAMTS-13 axis has emerged as a potential therapeutic target for both sepsis and COVID-19.…”
Section: Introductionmentioning
confidence: 99%